International law - Cassese, Antonio (Oxford ; New York : Oxford University Press, 2001)
This title covers major topics, providing a background to the history of international law whilst exploring developments in the field. Written specially for the student, this text covers all subjects found on an introductory course.
pt. I. Origins and foundations of the international community. The main legal features of the international community ; The historical evolution of the international community ; States as the primary subjects of international law ; Other international legal subjects ; The fundamental principles governing international relations -- pt. II. Creation and enforcement of international legal standards. International lawmaking: custom and treaties ; International lawmaking: other law-creating processes ; Implementation of international rules within national systems ; State responsibility ; Mechanisms for promoting compliance with international rules and pursuing the prevention or settlement of disputes ; Enforcement in the case of violations by states ; Enforcement in the case of violations by individuals -- pt. III. Contemporary issues in international law. The role of the United Nations ; Collective security and the prohibition of force ; Legal restraints on violence in armed conflict ; Protection of human rights ; Protection of the environment ; Legal attempts at narrowing the gap between North and South.
Includes bibliographical references (pages 419-454) and index.
Keywords: International law; Droit international; International law; 2; Volkenrecht; Droit international